The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/polym15244714
|View full text |Cite
|
Sign up to set email alerts
|

Recyclability of Post-Consumer Polystyrene at Pilot Scale: Comparison of Mechanical and Solvent-Based Recycling Approaches

Jean-Mathieu Pin,
Iman Soltani,
Keny Negrier
et al.

Abstract: Solvent-based and mechanical recycling technology approaches were compared with respect to each process’s decontamination efficiency. Herein, post-consumer polystyrene (PS) feedstock was recycled by both technologies, yielding recycled PS resins (rPS). The process feedstock was subjected to four recycling cycles in succession to assess the technology perennity. The physico-chemical and mechanical properties of the rPS were then evaluated to discern the advantages and drawbacks of each recycling approach. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…The same differences were observed for impact strength values, where the results for toughened samples were significantly better. Similar to the strain at break values, the Charpy test results revealed that for most of the materials the impact resistance was close to the results of brittle types of thermoplastics, such as poly(lactic acid)-PLA, or polystyrene-PS [59][60][61][62], which translates to being 2 kJ/m 2 or lower. A visibly more favorable deformation mechanism characterizes the IM-modified materials since most of the samples reached 15 kJ/m 2 in Charpy tests.…”
Section: Mechanical Performance-static Tensile Tests and Impact Resis...supporting
confidence: 64%
“…The same differences were observed for impact strength values, where the results for toughened samples were significantly better. Similar to the strain at break values, the Charpy test results revealed that for most of the materials the impact resistance was close to the results of brittle types of thermoplastics, such as poly(lactic acid)-PLA, or polystyrene-PS [59][60][61][62], which translates to being 2 kJ/m 2 or lower. A visibly more favorable deformation mechanism characterizes the IM-modified materials since most of the samples reached 15 kJ/m 2 in Charpy tests.…”
Section: Mechanical Performance-static Tensile Tests and Impact Resis...supporting
confidence: 64%